FILSAFAT BAHASA IBU DALAM PROSES PEMBELAJARAN - Yayuk Setyowati; Sudjarwo, sudjarwo; Muhammad Nurwahidin (JOEL: Journal of Educational and Language Research, 2022)
A person's or an individual's first language is their mother tongue. Mother tongue is obtained in the family environment, especially from the mother. Mother tongue is very important and must be maintained. The person who plays an important role in the acquisition of the first language or mother tongue is the mother. in the process of acquiring the first language, it will be acquired from the family. When it comes to acquiring a second language, however, one must make an effort to do so intentionally, specifically by learning. In everyday life, the mother tongue is very familiar to our ears. Even in formal forums, we still often meet them, in communication using the mother tongue, one example is at school. Students, particularly those in lower grades, still frequently use their mother tongue in classroom interactions, including those with friends and teachers. Therefore, the teaching and learning process in schools is greatly influenced by the mother tongue.This proves that mother tongue is very influential in the learning process at school. The following are the reasons why mother tongue-based learning activities are so important: (1) mother tongue is considered as a means of developing student character, (2) geography, (3) habits, (4) teacher's perception of using mother tongue in class as a strategy to attract attention. students, facilitating the absorption of material for students, (5) convenience, and (6) results.